Lifestyles and academic stress among health sciences students at the National University of Chimborazo, Ecuador: a longitudinal study - Salazar-Granizo, Yolanda E.; Hueso-Montoro, César; Caparros-Gonzalez, Rafael A. (Frontiers in Public Health, 2024)
Background The significant changes experienced by university students in their training are inherent to educational processes. Social isolation caused by the COVID-19 pandemic, online education and the reopening of higher-education institutions produced substantial variations in the lifestyle of university students in health sciences and generated academic stress and perceived stress. This study was conducted at the National University of Chimborazo (UNACH), a public institution located in Riobamba, central Ecuador, the diverse student's population provided an ideal setting for examining the interplay between academic and perceived stress, lifestyle factors, and learning modalities. The research focused on health sciences students across six academic programs. The university's geographical position and demographic characteristics offered a representative sample for investigating these factors within the context changing. Aim To compare academic and perceived stress and university students' lifestyles at two different periods: (1) during the mandatory social confinement caused by the COVID-19 pandemic with an online learning modality (T1); (2) in the post-pandemic period with a return to face-to-face activities (T2). Design An observational, analytical, quantitative, and longitudinal study. Participants Students from six programs (Nursing, Physiotherapy, Clinical Laboratory, Medicine, Dentistry, and Clinical Psychology) from the Faculty of Health of the National University of Chimborazo-Ecuador (n = 2,237) participated voluntarily, the students had one mean age of M = 21.31 (SD = 2.36) at T1 and M = 22.94 (SD = 2.40) at T2. Non-probability convenience sampling was employed due to the accessibility of the student population and the importance of including the maximum number of relevant individuals within the study population. Methods The following instruments were used: Nola Pender's Lifestyle Profile Questionnaire, Cognitive Systemic Inventory for the study of academic stress, and Cohen's Perceived Stress Scale. Results In T1 and T2, students reported high levels of stress, and increased unhealthy lifestyle increased with the return to classrooms. Additionally, upon returning to face-to-face activities (T2), the mean score applied to the responses of Nola Pender's Lifestyle Profile Questionnaire decreased from M = 113.34 (SD = 23.02) to M = 107.2 (SD = 29.70; p < 0.001). There was significant difference (p < 0.001) in academic stress in T1 [M = 66.25 (SD = 15.66)] and T2 [M = 64.00 (SD = 17.91)]. Conclusions Upon returning to university classrooms (T2), the number of students who reported an “unhealthy” lifestyle increased. Academic stress was high in T1 and T2 and was reported higher in online activities during social isolation.